VD_FINDINFO HC / 2012 / 591 vom 29. August 2012 - VD Tribunal cantonal (2012)
DIVORCE, OBLIGATION D'ENTRETIEN, ENFANT, COMPENSATION DE CRÉANCES | 120 al. 1 CO, 319 let. a CPC (CH), 320 CPC (CH), 322 al. 1 CPC (CH), 404 CPC (CH), 405 al. 1 CPC (CH)